2005
DOI: 10.2139/ssrn.1001630
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Model for Older Workers' Labor Transitions After a Health Shock

Abstract: In this work we study older workers' (50-64) labor force transitions after a health/disability shock. We find that the probability of keeping working decreases with both age and severity of the shock. Moreover, we find strong interactions between age and severity in the 50-64 age range and none in the 30-49 age range. Regarding demographics we find that being female and married reduce the probability of keeping work. On the contrary, being main breadwinner, education and skill levels increase it. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Riphahn (1999) finds that health shocks increase the probability of unemployment by 84% and the probability of dropping out of the labour force by 200% for individuals aged 40 to 59 in Germany. Jiménez-Martín et al (2006) find that, for Spanish workers aged between 50 and 64, the probability of continued working decreases with the severity of the shock. Smith (2004) also finds that, for individuals older than 50 who suffer a health shock, there is a 15% decrease in the probability of working.…”
Section: Health and Labour Market Outcomes: Previous Evidencementioning
confidence: 74%
“…Riphahn (1999) finds that health shocks increase the probability of unemployment by 84% and the probability of dropping out of the labour force by 200% for individuals aged 40 to 59 in Germany. Jiménez-Martín et al (2006) find that, for Spanish workers aged between 50 and 64, the probability of continued working decreases with the severity of the shock. Smith (2004) also finds that, for individuals older than 50 who suffer a health shock, there is a 15% decrease in the probability of working.…”
Section: Health and Labour Market Outcomes: Previous Evidencementioning
confidence: 74%
“…We are particularly interested in labour market transitions that are not led by the availability of retirement and therefore we restrict our population of interest to individuals below 60 years of age. Disney et al [18], and Jime´nez-Martin et al [19] for the Spanish case, have shown that adverse health shocks affect positively the probability of retirement and, to the extent that the replacement ratio of pensions is not 100%, part of income related health inequality could be explained by such transitions. In fact, Van Doorslaer and Koolman [12] find that it is the health and income distribution of the retired that explains income related health inequality in Denmark and Germany.…”
Section: Institutional Background and Outcomes Of Interestmentioning
confidence: 99%
“…Dorn and Sousa-Poza (2010) is a comparative study of the numerous alternatives available. They include, in particular, disability pensions (see, for example, Benitez-Silva et al (1999) or Rust et al (2002) for the United States and Borsch-Supan (2000), Jiménez-Martín et al (2006) and Lammers et al (2010) for the European case) and unemployment benefits (see Kyyrä and Ollikainen (2009), Giesecke and Kind (2013) or García Pérez and Sánchez Martín (2013)). We focus here on unemployment, which is a popular exit route in Spain (see eg, García-Pérez et al (2013)), as it is, too, in other European countries (see below).…”
Section: Introductionmentioning
confidence: 99%